DYING ON THE MOUNTAIN AND BEING BORN FOR ETERNITY. A STUDY ABOUT THE IMAGINARY. (Fiep Bulletin - online, 2014)
This paper aims at identifying the imaginary meaning climbers attribute to the fact they can die while they are climbing the mountains. For that purpose, a bibliographical survey was carried out in books about climbing high mountains in Brazil and in interviews with climbers. Although the adventurers can die on the mountain slopes, they are audacious enough to face those confrontations, trying to arrive at the top to register their names in an imaginary “book” with the names of those who were able to triumph over this challenge, in spite of the fact that they may have had to pay with their lives for their conquest. That is the reason why they attempt to have intense experience in their adventures on the mountain side while they struggle bravely against risks, giving their lives the highest possible value.